Knowledge and Perception about Ketogenic Diet - Abbas, Ruaa Qassim; AbdulRaheem, Yousif (Journal of Neonatal Surgery, 2025)
Background and Objectives: Obesity now is pandemic that many strategies are growing to cope with. Ketogenic diet, with its pros and cons, is one of the promising yet query obesity's treatment strategies. Objectives: This study was aimed to assess the prevalence of using Ketogenic diet as weight losing method among overweight and obese persons and the overall perception towards it.. The objective of this study was to determine the prevalence and Perception about ketogenic diet, its therapeutic uses, possible side effects and benefits among overweight and obese persons visiting primary health care centers in Baghdad. Methods: Cross sectional study conducted in Baghdad, on a convenient sample of 456 overweight and obese persons attending Family Medicine Based Primary Health Care Centers over a period from 1st September- 1st March 2023). A self-administered structural questionnaire was used for data collection and the persons were interviewed after taking informed consents. Results: One-thirds of participants were aware of Ketogenic diet as a weight losing method. Whereas the prevalence of being on Ketogenic diet was 18.2%. The awareness rate was found to be influenced mostly by age, gender and educational level. The majority had built their information according to what they read and saw on social media while specialists' support ranked last with only 12% depending on. Overall poor perception level was observed with Ketogenic diet followers, those who took their information from specialists and unemployed participants demonstrated the best perception's levels. Conclusion: Many people are familiar with the ketogenic diet, but much of what they believe comes from social media, where misinformation spreads easily. This gap between perception and reality leads to confusion about its actual benefits, side effects and needed follow up.